2011
DOI: 10.2174/138161211795222568
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Therapeutic Targeting of p53 in Cancer: One Size Does Not Fit All

Abstract: p53, the "guardian of the genome" and the most mutated gene in cancer presents a considerable therapeutic opportunity as well as a challenge. In the past decade, several therapeutic strategies have been developed that aim to take advantage of a wealth of knowledge about p53, including insights into the biology and patho-biology of p53. Nevertheless, considerable challenges remain, not least as a result of tissue- and cancer-specific differences in p53 regulation and/or function. p53 does not act in the same ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Hence a one-drug-fits-all approach may not be feasible for targeting TP53 mutations. 12 , 576 , 577 Therefore, different p53-targeting drugs may be required for different p53 mutants. Second, p53-targeted therapy alone may not be sufficient to treat cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Hence a one-drug-fits-all approach may not be feasible for targeting TP53 mutations. 12 , 576 , 577 Therefore, different p53-targeting drugs may be required for different p53 mutants. Second, p53-targeted therapy alone may not be sufficient to treat cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Multiple in vivo studies have revealed tissue specificity in p53-dependent gene expression. 20 25 Consistent with these DNA damage-triggered outcomes, restoration of p53 to tumors that arise because of p53 deletion show a distinct fate depending upon tissue, with sarcomas and liver carcinomas regressing because of senescence, while lymphomas undergo apoptosis. 26 , 27 It is noted that there is growing evidence that the p53 programs in response to acute DNA damage may be distinct from those involved in tumor suppression.…”
Section: Introductionmentioning
confidence: 88%
“…The p53 gene plays an important role in cell regulation with impact on aging processes and cancer (Seim et al., 2016; Tanikawa et al., 2017). However, the tissue‐specific nature of p53 gene expressions makes it difficult to develop targeted therapies (Vlatkovic et al., 2011). Thus, it is crucial to identify patterns in p53 gene expression that are shared and unique across multiple tissues.…”
Section: Analysis Of Multi‐tissue Gene Expression Datamentioning
confidence: 99%
“…The gene expression is often tissue‐specific. For instance, the p53 gene is critical for cell regulation playing prominent role in the cancer development (Tanikawa et al., 2017), however p53 tissue‐specific expression makes it difficult to develop targeted therapies (Vlatkovic et al., 2011). It is thus crucial to identify patterns in gene expression that are shared and unique across multiple tissues.…”
Section: Introductionmentioning
confidence: 99%